Elucidating atomistic mechanisms of the formation of phase-controlled ultrathin MoTe2 films and lateral hetero-phase MoTe2 interfaces - Kim, Hyeonkyeong; Bhang, Jooyong; Park, Taejoon; Lee, Jae Hyun; Seo, Hosung; Yoo, Youngdong (Surfaces and Interfaces, 2023)
Molybdenum ditelluride (MoTe2) is gaining great attention because of its phase tunability. However, the precise control of the phase of ultrathin MoTe2 films is quite challenging, and the atomistic mechanism has not been fully elucidated. Here, we establish phase-controlled growth of ultrathin MoTe2 films by independently adjusting the Te atomic flux. We employed a chemical vapor deposition method that uses Mo nanolayers as a precursor to synthesize ultrathin MoTe2 films with a thickness of 4 − 7 nm. We found that ultrathin 1T’ MoTe2 films were formed with low Te atomic flux, whereas ultrathin 2H MoTe2 films were obtained with high Te atomic flux. Lateral metal–semiconductor hetero-phase 1T’/2H MoTe2 ultrathin films with seamless interfaces were synthesized with medium Te atomic flux. Furthermore, we performed density functional theory calculations to elucidate the detailed mechanisms of the phase transition between 1T’ and 2H MoTe2 driven by Te vacancy as well as the property of the 1T’/2H MoTe2 interface. This work provides a full understanding of the formation of phase-controlled ultrathin MoTe2 films and lateral metal–semiconductor hetero-phase MoTe2 interfaces.
Keywords: Hetero-phase interfaces; Phase control; Te vacancies; Ultrathin MoTe2 films